Respuesta :
we have that
2x+2+4x---------> expression A
and
2(3x+1)----------> expression B
expression A=2x+2+4x--------> (2x+4x)+2----------> 6x+2
expression A=6x+2
expression B=2(3x+1)------> 2*3x+2*1---------> 6x+2
expression B=6x+2
therefore
expression A=expression B------------> the two expressions are equivalent
so
if the expression A for x=2 is 14
the expression B for x=2 also is 14
the answer Part A)
the value of the second expression when x=2 is 14
the answer Part B) the two expressions are equivalent
let's check it
for x=2
expression B=6x+2--------> 6*2+2-----> 14
the answer is the option C.)
The value of the second expression is 14, so the expressions are equivalent.
2x+2+4x---------> expression A
and
2(3x+1)----------> expression B
expression A=2x+2+4x--------> (2x+4x)+2----------> 6x+2
expression A=6x+2
expression B=2(3x+1)------> 2*3x+2*1---------> 6x+2
expression B=6x+2
therefore
expression A=expression B------------> the two expressions are equivalent
so
if the expression A for x=2 is 14
the expression B for x=2 also is 14
the answer Part A)
the value of the second expression when x=2 is 14
the answer Part B) the two expressions are equivalent
let's check it
for x=2
expression B=6x+2--------> 6*2+2-----> 14
the answer is the option C.)
The value of the second expression is 14, so the expressions are equivalent.